An Evaluation of Agricultural Enterprises’ Information Needs - Stabingis, Linas (Ekonomika, 1997)
The paper deals with the main problems of defining the needs of all enterprises’ economical information users. To solve these problems, it is necessary to dearly define all groups of the enterprises’ economical information users, improve the content of financial and statistical accountability for successful macroeconomic regulation, and investigate the detailization principles of the enterprises’ internal economical information user needs. As a result of the research. suggestions for solving the above mentioned problems in the agricultural enterprises of Lithuania arc given in the paper.